ROLE OF NATIONAL COMMISSION FOR WOMEN IN WOMEN’S EMPOWERMENT - Mrs. Licy Varghese (Galaxy International Interdisciplinary Research Journal, 2022)
Empowerment is the process that allows women to be independent and gain access to control the material as well as human resources. Empowerment is the redistribution of power and provides equal opportunities to women in the male dominating society. Women empowerment is considered as one of the prime concerns for today’s government as participation of women in various fields including social, economical, and political plays an important role in the country’s development and growth. Participation of women in politics is considered an important factor that helps in the empowerment of women as it improves their decision-making ability. In 1992, the National Commission for Women set up safeguards for the constitutional legal right of women. All the matters and affairs related to women are investigated and examined through the national commission to empower women in the patriarchal world.